Pengaruh Literasi Masyarakat terhadap Kesiapsiagaan dalam Menghadapi Bencana Lahar Dingin di Nagari Parambahan - Khairiah Putri; Rahmadhona Fitri Helmi (YASIN, 2026)
Although cold lahar floods are disasters that have the potential to cause substantial losses, community preparedness among those who have no experience in facing similar threats still needs to be strengthened through disaster literacy. This study aims to analyze the effect of disaster literacy on community preparedness in facing cold lahar flood disasters in Nagari Parambahan, Lima Kaum Subdistrict, Tanah Datar Regency. This study used a descriptive quantitative approach with a survey design, involving 78 respondents selected through a two-stage cluster sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression. The results showed that disaster literacy had a positive and significant effect on community preparedness, as indicated by a calculated t-value of 3.897 > t-table value of 1.992 with a significance level of 0.001 < 0.05. The regression equation obtained was Y = 36.023 + 0.371X, while the coefficient of determination (R²) of 0.167 indicated that disaster literacy contributed 16.7% to community preparedness. These findings confirm that disaster literacy plays an important role in improving community preparedness for the risk of cold lahar floods. The implications of this study contribute to the development of disaster risk management studies at the community level and serve as a practical reference for local governments and disaster management agencies in strengthening education, outreach, and disaster risk reduction programs on an ongoing basis.